Initial teacher training for primary and secondary education in Germany, Spain, Finland, France and United Kingdom. Comparative study - Teresa Rebolledo Gámez (Universidad Nacional de Educación a Distancia (UNED), 2015)
The initial teacher training provides the skills and tools necessary for this confronted with the transformations of a changing and dynamic society. In Europe, the inicial training teachers for primary and secondary education is characterized by diversity in their approaches. Taking as reference the countries of Germany, Spain, Finland, France and the UK, we have analyzed different issues which can obtain a European panorama in relation to initial teacher training. Although the trend towards internationalization and standardization of university education, the confluence of different approaches depending on the idiosyncrasy of the regions where are inserted.